Intensified texture of Zr702 sheet after slow cooling from near β-transus temperature. Issue 15 (13th October 2019) - Zeng, Lingguo; Zhu, Yufan; Li, Zhijun; Chai, Linjiang; Chen, Ke; Pan, Hucheng; Yang, Zhinan; Guo, Ning; Yang, Changlin
ABSTRACT: Microstructures and textures of a Zr702 sheet subjected to slow cooling (air cooling (AC) and furnace cooling (FC)) from a near β-transus temperature (980°C) were characterised by electron channelling contrast imaging and electron backscatter diffraction techniques. Results show that textural intensities of both the AC and the FC are markedly higher than that of the initial specimen and the FC specimen owns the strongest texture. After both the heat treatments, the initial bimodal basal textural features are retained with the recrystallisation textural component (0°, 30°, 30°) becoming dominant but the deformation textural component (0°, 30°, 0/60°) largely weakened. The textural intensification is attributed to strong variant selection during the β → α phase transformation and slow cooling-induced sufficient growth of residual prior α grains.